Biostimulants and Steiner solution in growth and production of Capsicum annuum L. - Buelna-Tarín, Salomón; Romero-Félix, Celia Selene; Bojórquez-Ramos, Cosme; Lugo-García, Gabriel Antonio; Sánchez-Soto, Bardo Heleodoro (Revista Mexicana de Ciencias Agrícolas, 2024)
The use of biostimulants is an alternative to improve the assimilation of nutrients by the plant, whether applied in irrigation water or foliarly. This research aimed to evaluate the effect of the Steiner nutrient solution and the foliar application of three biostimulants on growth and yield parameters of two cultivars of jalapeño pepper (Capsicum annuum L.) under greenhouse conditions. Four treatments were established under a randomized complete block design with four repetitions, in Juan José Ríos, Ahome, Sinaloa in October 2018. The variables evaluated were plant height, stem diameter, leaf dry weight, stem dry weight, fruit length, number of fruits per plant, total fruit weight, fruit weight per plant and number of flowers. The Giberelin 10 biostimulant had a significant effect on plant height. The Bronco cultivar, on average of treatments, was outstanding for presenting high values in the growth and yield parameters evaluated, except for stem diameter and fruit length, which were higher in the Forajido cultivar. The Forajido cultivar showed a higher plant height due to the effect of the Giberelin 10 treatment, while Bronco exhibited a higher number of fruits per plant with the Fiamin-fol treatment and a higher fruit weight per plant with the treatments of Maxi-Grow Excel and the Steiner nutrient solution (control).
Keywords: growth; jalapeño pepper; nutrient solution; yield